PERBANDINGAN EXPECTED RATE OF RETURN DENGAN RATE OF RISK DALAM MENILAI HARGA SAHAM PADA PT. UNILEVER INDONESIA,TBK - Dewi, Trina (EKONOMIA, 2013)
By the result of the analysis and study, we could say that the Expected Rate of Return of 183.3%, in 2009 was higher , than the Expected Rate of Return in 2010 , which was only 8.12%. It is caused the rate of Return Market in 2009 was higher than rate of Return Market in 2010 was, the indicator of Beta that was >1, also influenced the Expected Rate of Return in 2009. The Risk-free interest rate could raise the rate and increase the chance of getting a profit. If we look at the Rate of Risk, the Rate of Risk only increased from 21.92% in 2009 to 23,82% in 2010.